Effect of different stabilization methods on the proximate compositions of Brewer's rice - Muhamad Nordin, Nik Nor Adilah; Karim, Roselina; Mohd Ghazali, Hasanah; Mohd Adzahan, Noranizan (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Brewer’s rice is one of the by-product that is derived from rice milling processes. It has been considered as unutilized materials due to its high susceptibility to lipid oxidation, even though it contained valuable food ingredients. In the present study, the effect of microwave heating, gamma irradiation, and hydrochloric acid (HCl) treatment on Brewer’s rice stabilization was investigated. The effect of stabilization method on the free fatty acid (FFA) content and proximate composition of Brewer’s rice were monitored during storage at ambient temperature. The FFA content in Brewer’s rice increased significantly (p<0.05) during storage time for all stabilization methods, except for HCl treatment. No significant (p<0.05) effect of stabilization treatment was observed on the protein, fat, and ash contents of Brewer’s rice as compared to the control. Microwave and chemical methods significantly (p<0.05) reduced the moisture content, but significantly (p<0.05) increased the carbohydrate after 16 weeks of storage. Microwave heating was able to reduce the oxidation of Brewer’s rice without influencing the proximate composition of Brewer’s rice. Therefore, it can be considered as the most suitable stabilization method to inhibit rancidity.